A Tool Model Group (TMG) Development to Enhance Student Performance - Tawafak R.M.; Alsewari A.A.; Malik S.I.; Alfarsi G. (Institute of Electrical and Electronics Engineers Inc., 2023)
E-learning; Education computing; Students; Academic performance; Assessment method; Development and challenges; E - learning; Educational institutions; Group development; Model groups; Student performance; TEL; Tool models; Learning systems